Liver transplantation for unresectable colorectal liver metastases in patients and donors with extended criteria (SECA-II arm D study). Issue 3 (25th April 2020) - Smedman, T M; Line, P-D; Hagness, M; Syversveen, T; Grut, H; Dueland, S
Abstract: Background: Patients with metastatic colorectal cancer receiving palliative chemotherapy have a 5-year survival rate of approximately 10 per cent. Liver transplantation using strict selection criteria in patients with colorectal cancer and unresectable liver-only disease will result in a 5-year survival rate of 56–83 per cent. The aim of this study was to evaluate survival of patients with colorectal liver metastases (CRLM) after liver transplantation using extended criteria for both patients and donors. Methods: This was a prospective single-arm study. Patients with synchronous unresectable CRLM who were not suitable for arms A, B or C of the SEcondary CAncer (SECA) II study who had undergone radical resection of the primary tumour and received chemotherapy were included; they underwent liver transplantation with extended criteria donor grafts. Patients who had resectable pulmonary metastases were eligible for inclusion. The main exclusion criteria were BMI above 30 kg/m 2 and liver metastases larger than 10 cm. Survival was estimated using Kaplan–Meier analysis. Results: Ten patients (median age 54 years; 3 women) were included. They had an extensive liver tumour load with a median of 20 (range 1–45) lesions; the median size of the largest lesion was 59 (range 15–94) mm. Eight patients had (y)pN2 disease, six had poorly differentiated or signet ring cell-differentiated primary tumours, and five had primary tumour in the ascending colon. The median Fong clinical risk score was 3 (range 2–5) and the median Oslo score was 1 (range 1–4). The median plasma carcinoembryonic antigen level was 4·3 (range 2–4346) μg/l. Median disease-free and overall survival was 4 and 18 months respectively. Conclusion: Patients with unresectable liver-only CRLM undergoing liver transplantation with extended patient and donor criteria have relatively short overall survival. Graphical Abstract: Patients with extensive liver tumour load and a mainly poorly differentiated N2 primary tumour have short overall survival from the time of liver transplantation. Relapses were mostly unresectable and the patients had short survival from the time of relapse. These patients should not be offered liver transplantation. Extended criteria leads to relatively short survival.